2017
DOI: 10.1097/md.0000000000007929
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of medication appropriateness and frailty among residents of aged care homes in Malaysia

Abstract: Aging is significantly associated with the development of comorbid chronic conditions. These conditions indicate the use of multiple medications, and are often warranted by clinical guidelines. The aim of the present study was to evaluate medication appropriateness and frailty among Malaysian aged care home residents with chronic disease. The participants were 202 elderly (≥65 years) individuals, a cross-sectional sample from 17 aged care homes. After ethics approval, each participant was interviewed to collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 43 publications
3
31
0
4
Order By: Relevance
“…Consistent with previous studies using both versions 1 and 2 of the STOPP criteria, this study identified a significant association between polypharmacy (>5 medications) and prescription of at least one PIM [25,30,32,33,[35][36][37][38][39][40][41][42][43][44][45]. The association between PPO occurrence and polypharmacy identified in this study has been less consistently reported elsewhere [33,36,37,46].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Consistent with previous studies using both versions 1 and 2 of the STOPP criteria, this study identified a significant association between polypharmacy (>5 medications) and prescription of at least one PIM [25,30,32,33,[35][36][37][38][39][40][41][42][43][44][45]. The association between PPO occurrence and polypharmacy identified in this study has been less consistently reported elsewhere [33,36,37,46].…”
Section: Discussionsupporting
confidence: 88%
“…Published studies which have applied version 2 of the STOPP criteria report PIM prevalence of between 39.1% and 56.1% in older adults in the community and long-term care setting, and 42.1% to 88.5% in the inpatient setting [25][26][27][28][29][30][31][32][33][34]. The higher reported prevalence in the inpatient setting is likely a reflection of greater co-morbidity and prescription medication burden.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the screening of the full texts, 62 articles were excluded because they did not meet the inclusion criteria. Therefore, 25 publications were ultimately selected and included in the review (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…. The prevalence of frailty ranged between 6.2% and 76% . Regarding study setting, 13 studies included community‐dwelling individuals, five studies included hospitalized patients in acute units and the rest included outpatients, care home residents or mixed populations.…”
Section: Resultsmentioning
confidence: 99%